Sleep quality and correlates of poor sleep in patients with rheumatoid arthritis. Issue 12 (December 2015) - Løppenthin, K.; Esbensen, B.; Jennum, P.; Østergaard, M.; Tolver, A.; Thomsen, T.; Midtgaard, J.
Abstract The objective of this study is to examine sleep quality and correlates of poor sleep in patients with rheumatoid arthritis (RA). Five hundred patients with RA were recruited from a rheumatology outpatient clinic and included in this cross-sectional study. Sleep quality and disturbances were assessed using the Pittsburgh Sleep Quality Index (PSQI). Other instruments included the Multidimensional Fatigue Inventory, the Epworth Sleepiness Scale, and the Health Assessment Questionnaire. Disease activity was assessed according to disease activity score DAS28-CRP-based. Complete scores on PSQI were obtained from 384 patients (77 %). In those, the prevalence of poor sleep (PSQI >5) was 61 %, and the mean global PSQI score was 7.54 (SD 4.17). A linear association was found between poor sleep and mental fatigue, reduced activity related to fatigue, physical fatigue, and general fatigue. Mental fatigue and general fatigue were independently associated with sleep quality, sleep latency, sleep duration, sleep efficiency, and daytime dysfunction. However, in the linear multivariate analysis, only general fatigue 1.06 (95 % CI 1.03–1.09) and mental fatigue 1.03 (95 % CI 1.01–1.05) were found to be significant correlates for reporting poor sleep. This study shows that a majority of patients with RA experience poor sleep and that general fatigue and mental fatigue are associated with poor sleep.